2022
DOI: 10.1177/13591045221075527
|View full text |Cite
|
Sign up to set email alerts
|

The association of attachment, mentalization and reflective functioning with mental health in gender diverse children and adolescents: A systematic review

Abstract: Gender diverse children (here defined as minors under 18) face greater risk for depression, anxiety and suicidality than their cisgender peers. This situation calls for research on protective factors of mental health in this population, and on appropriate therapeutic and supportive interventions. This systematic review aimed at (1) examining literature on the role of attachment, mentalization and reflective functioning in protecting mental health of gender diverse children and identifying the mental health out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Strategies aimed at improving reflective functioning and attachment have the capacity to reduce parental stress ( Nijssens et al, 2018 ), which may subsequently improve the health of the caregiver-child dyad. Mentalization and reflective functioning appears to be particularly important in gender diverse children and adolescents ( Caldarera et al, 2022 ), which is significant considering roughly 15 % of the participants in this study identified with a non-binary gender. The BBR specifically addresses caregiver-child relations through attachment-based work that is highly encouraged.…”
Section: Discussionmentioning
confidence: 79%
“…Strategies aimed at improving reflective functioning and attachment have the capacity to reduce parental stress ( Nijssens et al, 2018 ), which may subsequently improve the health of the caregiver-child dyad. Mentalization and reflective functioning appears to be particularly important in gender diverse children and adolescents ( Caldarera et al, 2022 ), which is significant considering roughly 15 % of the participants in this study identified with a non-binary gender. The BBR specifically addresses caregiver-child relations through attachment-based work that is highly encouraged.…”
Section: Discussionmentioning
confidence: 79%